Prevalence and factors associated with fear of hypoglycaemia among adults with Type 1 diabetes mellitus at an academic hospital in South Africa. (2021) - Tshabalala, Amme Mardulate; Ajidahun, Adedayo Tunde; Mkhabela, Treginah; Bapela, Phemelo; Majumane, Constance; Msimango, Tshepo
Abstract: Hypoglycaemia is one of the most common and acute complications in the management of diabetic patients. The study conducted at an academic hospital in Johannesburg, Gauteng province, South Africa, purposed to determine the prevalence and risk factors for fear of hypoglycaemia in Type 1 Diabetes Mellitus patients. This cross-sectional study used the 15-item Fear of Hypoglycaemia (FH) scale to collect data from patients diagnosed with Type 1 Diabetes Mellitus and on insulin therapy at an academic hospital in Johannesburg. Patients with a score of 22 or more were classified as suffering from fear of hypoglycaemia. The prevalence of FH was 64.4%. Participants with FH were significantly younger by 10 years – than those with no FH (p = 0.012). There was no significant association between certain socio-demographic variables and FH, or between the monitoring of blood glucose levels and FH (p = 0.448). However, there was a significant association between the monitoring of blood glucose levels and worrying about hypoglycaemia (p = 0.021). This study reported high levels of fear of hypoglycaemia and an association between the monitoring of blood glucose levels and anxiety about hypoglycaemia. The diabetic condition of most of the participants was found to be is well controlled.